Penguatan Literasi Digital dan Inovasi Kewirausahaan UMKM melalui Program Pengabdian Masyarakat Berbasis AI Marketing - Muflihah, Muflihah; Indrayono, Yohanes; Primata, Lusiana Ratna; Lupiyanto, Lupiyanto (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This community service activity was carried out as an effort to address the issue of low levels of innovation and entrepreneurial behaviour among MSME actors in the Bojong Rangkas Tourism Village, Bogor Regency. Through training on Artificial Intelligence (AI) Marketing and financial literacy, the service team aimed to foster digital adaptation skills and innovative entrepreneurial behaviour. The activity employed methods such as lectures, demonstrations, and hands-on mentoring sessions involving 30 local MSME participants. The results showed a 68% increase in participants’ understanding of AI-based digital marketing concepts, as well as a rise in motivation to develop product innovations and marketing strategies. The main inhibiting factors were limited digital infrastructure and participants’ low self-confidence in using new technologies. This programme is expected to encourage more adaptive, creative, and innovation-oriented entrepreneurial behaviour among MSME actors.